2013
DOI: 10.1371/journal.pone.0055752
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Gene Expression of Proprotein Convertases in Human Lung Cancer Have a Limited Number of Scenarios

Abstract: Proprotein convertases (PCs) is a protein family which includes nine highly specific subtilisin-like serine endopeptidases in mammals. The system of PCs is involved in carcinogenesis and levels of PC mRNAs alter in cancer, which suggests expression status of PCs as a possible marker for cancer typing and prognosis. The goal of this work was to assess the information value of expression profiling of PC genes. Quantitative polymerase chain reaction was used for the first time to analyze mRNA levels of all PC gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 59 publications
(58 reference statements)
1
20
0
Order By: Relevance
“…observed a selective and strong furin mRNA expression in lung cancer tissues derived from non‐small cell lung cancer (NSCLC), but not in those derived from small cell lung cancer (SCLC) . Other studies detected high furin mRNA levels in lung squamous cell carcinomas and adenocarcinomas of the lungs . Moreover, furin mRNA and protein levels appeared to correlate with the invasive potential of NSCLC cell lines and furin protein expression was found in the majority of invasive squamous cell carcinomas (SCC) of the lung .…”
Section: Furin Promotes Tumour Progressionmentioning
confidence: 98%
See 2 more Smart Citations
“…observed a selective and strong furin mRNA expression in lung cancer tissues derived from non‐small cell lung cancer (NSCLC), but not in those derived from small cell lung cancer (SCLC) . Other studies detected high furin mRNA levels in lung squamous cell carcinomas and adenocarcinomas of the lungs . Moreover, furin mRNA and protein levels appeared to correlate with the invasive potential of NSCLC cell lines and furin protein expression was found in the majority of invasive squamous cell carcinomas (SCC) of the lung .…”
Section: Furin Promotes Tumour Progressionmentioning
confidence: 98%
“…Functional studies showed that inhibition of furin activity, either through genetic silencing or through application of the inhibitors PDX or CMK, decreases processing of the insulin‐like growth factor 1 receptor (IGF1R), cell proliferation, in vitro migration and invasion abilities, as well as in vivo tumour growth . These observations indicate that furin expression is not only a potential marker, but also a potential therapeutic target for lung carcinomas.…”
Section: Furin Promotes Tumour Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, furin is an attractive candidate as a therapeutic target in human cancer because it is overexpressed in human cancer cell lines and primary squamous cell carcinomas from lung, head, and neck among many others . In addition, previous reports on PCs and cancer describe the increase expression of PCs in primary lung cancers and the possible use of furin as a tumor marker, that is, furin is overexpressed in non‐small cell lung carcinoma and not in small cell carcinomas and has been proposed as a marker to differentiate between these two tumor types . Given furin's role in processing cancer relevant substrates, its inhibition could open a new therapeutic alternative, either used alone or in combination with other drugs in the treatment of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…At the RNA level, the changes are seen in transcription and post-transcriptional modifications [4,13], and at the protein level, it is seen at the translation and post-translational effects [23,24] as depicted in Figure 1.…”
Section: Molecular Alterations For Cancer Diagnosismentioning
confidence: 99%